The Psychological Problems in Sexual Deviation of Christian Grey in Fifty Shades Movies - Putri Rokhma Afifa; Dian Maya Kurnia (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
The research applied psychoanalysis and psychological approaches to analyze Christian’s sexual deviation in Fifty Shades movies. This research used descriptive qualitative method to analyze the data. The research aimed at analyzing the causes of Christian’s sexual deviation and the personality impact of his sexual deviation. The objects of this research were the first and second movies of Fifty Shades trilogy, they were Fifty Shades of Grey and Fifty Shades Darker. The data of this research were taken from Christian’s dialogues, utterances, and actions related to the topic of this research. The findings of this research showed that Christian had sexual deviation related to sadistic things from his traumatic experience. Christian also had personality disorders as the impact of his sexual deviation. Christian had three personality disorders: histrionic, obsessive-compulsive, and narcissistic personalities.